2021
DOI: 10.1590/1516-4446-2019-0685
|View full text |Cite
|
Sign up to set email alerts
|

Influence of migration on the thought process of individuals at ultra-high risk for psychosis

Abstract: Objective: To assess the influence of migration on the psychopathological presentation of individuals at ultra-high risk for psychosis (UHR) in Sã o Paulo, Brazil. Methods: This study is part of the Subclinical Symptoms and Prodromal Psychosis (SSAPP) project, a cohort study in Sã o Paulo, Brazil, designed to follow individuals at UHR. After screening with the Prodromal Questionnaire (PQ) and a clinical interview, the Global Assessment of Functioning (GAF) was administered, a neuropsychological assessment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Poverty of thought is more pronounced in the less educated patients 39 , and those with parents from lower socioeconomic status (especially in female patients 53 ). More recently, Nogueira and colleagues reported a relative excess of formal thought disorder among individuals with familial migration history at ultra-high risk of psychosis, though this study was limited by its sample size 54 . Nevertheless, these findings resonate with Berg and colleagues 55 who showed in a large Norwegian sample (n = 1081) that while natives and immigrants had mostly similar symptom profile, the most prominent difference in symptom dimensions, especially in visible minorities, related to disorganisation factor of PANSS (especially, difficulties in abstract thinking).…”
Section: Social Determinants Of 'Formal Thought Disorder'mentioning
confidence: 84%
“…Poverty of thought is more pronounced in the less educated patients 39 , and those with parents from lower socioeconomic status (especially in female patients 53 ). More recently, Nogueira and colleagues reported a relative excess of formal thought disorder among individuals with familial migration history at ultra-high risk of psychosis, though this study was limited by its sample size 54 . Nevertheless, these findings resonate with Berg and colleagues 55 who showed in a large Norwegian sample (n = 1081) that while natives and immigrants had mostly similar symptom profile, the most prominent difference in symptom dimensions, especially in visible minorities, related to disorganisation factor of PANSS (especially, difficulties in abstract thinking).…”
Section: Social Determinants Of 'Formal Thought Disorder'mentioning
confidence: 84%
“…In terms of psychosis-risk symptoms among migrants, one Brazilian study with a small sample ( N = 42; n migrants = 5) found higher levels of “thought disturbances” among participants with migration history compared to those without ( 65 ). Beyond this study and those examining the link between migration and transition rates from CHR to full-threshold psychosis, there has been limited research on the connections between immigration status and the CHR phase.…”
Section: Specific Contextual Factorsmentioning
confidence: 99%